2019
DOI: 10.1038/s41598-019-39386-w
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in the Effects of Prenatal Bisphenol A Exposure on Genes Associated with Autism Spectrum Disorder in the Hippocampus

Abstract: Autism spectrum disorder (ASD) is a neurodevelopmental disorder inexplicably biased towards males. Although prenatal exposure to bisphenol A (BPA) has recently been associated with the ASD risk, whether BPA dysregulates ASD-related genes in the developing brain remains unclear. In this study, transcriptome profiling by RNA-seq analysis of hippocampi isolated from neonatal pups prenatally exposed to BPA was conducted and revealed a list of differentially expressed genes (DEGs) associated with ASD. Among the DEG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
70
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(73 citation statements)
references
References 86 publications
(94 reference statements)
3
70
0
Order By: Relevance
“…To examine the effects of prenatal BPA exposure on the expression of genes associated with AD, we obtained transcriptome profiling data from RNA-seq analysis of hippocampal tissues isolated from six independent litters prenatally exposed to BPA (male n = 3; female n = 3) or a vehicle control (male n = 3; female n = 3) from the NCBI Gene Expression Omnibus (GEO) DataSets database (Accession: GSE140298; https://www.ncbi.nlm.nih.gov/gds/). As reported by Thongkorn et al (2019), when all male and female rat pups under the same treatment conditions were combined into one group, as many as 5,624 transcripts corresponding to 4,525 genes were significantly differentially expressed in the hippocampal tissues of BPA-treated rats ( Supplementary Table S1). When each sex was analyzed separately, a total of 2,496 transcripts (corresponding to 1,633 genes) and 4,021 transcripts (corresponding to 2,780 genes) in the hippocampal tissues of BPA-treated male and female pups, respectively, were significantly differentially expressed compared to those in the hippocampal tissues of controls (P-value < 0.05 and FDR < 0.05, (Supplementary Tables S2,S3).…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…To examine the effects of prenatal BPA exposure on the expression of genes associated with AD, we obtained transcriptome profiling data from RNA-seq analysis of hippocampal tissues isolated from six independent litters prenatally exposed to BPA (male n = 3; female n = 3) or a vehicle control (male n = 3; female n = 3) from the NCBI Gene Expression Omnibus (GEO) DataSets database (Accession: GSE140298; https://www.ncbi.nlm.nih.gov/gds/). As reported by Thongkorn et al (2019), when all male and female rat pups under the same treatment conditions were combined into one group, as many as 5,624 transcripts corresponding to 4,525 genes were significantly differentially expressed in the hippocampal tissues of BPA-treated rats ( Supplementary Table S1). When each sex was analyzed separately, a total of 2,496 transcripts (corresponding to 1,633 genes) and 4,021 transcripts (corresponding to 2,780 genes) in the hippocampal tissues of BPA-treated male and female pups, respectively, were significantly differentially expressed compared to those in the hippocampal tissues of controls (P-value < 0.05 and FDR < 0.05, (Supplementary Tables S2,S3).…”
Section: Resultsmentioning
confidence: 62%
“…In vivo studies have shown that maternal BPA exposure can disrupt brain functions and induce aggression 29 , anxiety 30 , cognitive deficits 30 , and learning-memory impairment in offspring mice 31 . Recently, our transcriptome profiling analysis of rat hippocampus revealed that maternal BPA exposure dysregulated genes associated with autism in the offspring hippocampus 32 . In addition to genes linked to autism, several genes were also found to be associated with AD.…”
mentioning
confidence: 99%
“…In light of previous studies, it is also known that BPA may impair the functioning of internal organs and systems, including (among others) the nervous, gastrointestinal, cardiovascular, reproductive, and excretory systems [1,2]. Moreover, some investigations have shown a correlation between the degree of exposure to BPA and the risk of diabetes, heart attack, neoplasms, and even autism [1][2][3][4].…”
Section: Introductionmentioning
confidence: 97%
“…Prenatal BPA exposure of Wistar rats causes changes in the hippocampal expressions of genes associated with ASD in a sex-specific manner. BPA disrupts the expression of ASD candidate genes (Auts2, Foxp2, and Smarcc2) more significantly in the male hippocampus than in females [130]. Subcutaneous injection of 20 µg BPA/kg BW/day in pregnant mice resulted in impaired neurotransmission.…”
Section: Neurotoxicitymentioning
confidence: 97%